The owl question : poems - Shearin, Faith (May Swenson Poetry Award series., 2002)
"The Owl Question underscores and relishes life's transitions from young girl to woman, from child to wife to mother, and from isolation to connection this poet's bright sense of abundance and awe, here expressed in finely tuned detail and refreshingly open observation, reads like a collective memory. Though private and closely held, these questionings are as familiar as our own souls, and in their transformation to poetry, Shearin has created the very "map" she wishes to guide her when she "can't learn the world fast enough.""--Publisher's description